Efficacy and safety of Dengzhan Shengmai capsule in the treatment of chronic heart failure: a systematic review and meta-analysis - Lu, Shenghua; Yu, Yunfeng; Dai, Sisi; Hu, Yaqi; He, Qin; Liu, Rongzhen; Liu, Jianhe (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDengzhan Shengmai Capsule (DZSMC) is a potential treatment for chronic heart failure (CHF). However, its specific benefits in the treatment of CHF remain unclear.MethodsRelated randomized controlled trials were searched in eight databases up to January 28, 2025, and included studies were determined according to the inclusion criteria. Subsequently, the basic characteristics and data from these studies were recorded using Excel 2010. Outcome-related data were subsequently imported into Revman 5.3 for meta-analysis.ResultsFifteen randomized controlled trials with 1606 patients were included in this meta-analysis. The results showed that compared to conventional treatment group, DZSMC combination group significantly improved the clinical effective rate [RR = 1.21, 95% CI (1.16,1.26), P < 0.00001], brain natriuretic peptide (BNP) [MD = −112.60, 95%CI (−212.23, −12.96), P = 0.03], N-terminal pro-B-type natriuretic peptide (NT-proBNP) [MD = −88.27, 95%CI (−108.11, −68.42), P < 0.00001], left ventricular ejection fraction (LVEF) [MD = 6.42, 95% CI (5.57, 7.27), P < 0.00001], left ventricular end-diastolic diameter (LVEDD) [MD = −5.72, 95% CI (−7.56, −3.87), P < 0.00001], left ventricular end-systolic diameter (LVESD) [MD = −5.33, 95% CI (−7.41, −3.26), P < 0.00001], left ventricular end-systolic volume (LVESV) [MD = −20.71, 95% CI (−34.59, −6.82), P = 0.003], and 6 min walk test [MD = 51.90, 95%CI (19.08, 84.72), P = 0.002], while adverse events had no significant difference [RR = 0.70, 95%CI (0.42, 1.17), P = 0.17]. Funnel plots indicated no publication bias for BNP, NT-proBNP, LVEF, and LVESD, while potential bias was observed for other outcomes.ConclusionDZSMC effectively improves clinical symptoms, cardiac function, and ventricular remodeling in CHF patients, with good safety, making it a potential adjuvant therapy for CHF. However, further research is needed to explore the long-term safety of DZSMC in order to enrich clinical evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024507368, PROSPERO [CRD42024507368].